Crossover point and maximal fat oxidation training effects on blood lipid metabolism in young overweight women: a pilot study - Wang, Dizhi; Zhang, Peizhen; Li, Jin (Frontiers in Physiology, 2023)
Purpose: To determine the effects of weight reduction schemes using the exercise intensities corresponding to maximal fat oxidation (FATmax) and crossover point (COP). The effects of different intervention protocols on blood lipid metabolism were compared to explore how fat can be consumed and used more efficiently and provide a theoretical basis for weight loss through exercise. Methods: This study included 30 young overweight women randomly divided into the COP, FATmax, and control groups. Participants in the COP and FATmax groups exercised for 45 minutes four times a week for eight weeks after the individual treadmill exercise test. The control group did not perform any exercise. Results: After eight weeks of training, participants in the COP group significantly decreased weight (2.6 ± 3.3 kg), body mass index (0.91 ± 1.26 kg/m2), body fat percentage (1.21 ± 1.50%), and fat mass (1.90 ± 2.30 kg) (P < 0.05). They also had significantly decreased hip circumference (4.8 ± 3.3cm), serum apolipoprotein B (ApoB) levels (15.48 ± 14.19 mg/dL), and ApoB/apolipoprotein AI (ApoAI) ratios (0.47 ± 0.37) (P < 0.01). However, their serum ApoAI levels were significantly increased (14.18 ± 10.24 mg/dL; P < 0.01). Participants in the FATmax group had significantly decreased hip circumference (2.4 ± 2.0 cm), serum ApoB levels (14.49 ± 11.00 mg/dL), and ApoB/ApoAI ratios (0.59 ± 0.30) (P < 0.01) but significantly increased serum ApoAI levels (29.53 ± 13.29 mg/dL; P < 0.01). No significant changes in physiological indexes were observed in participants in the control group. Conclusion: Personalised exercise intervention positively affected central obesity, effectively improving blood lipid metabolism and fat oxidation, reducing cardiovascular disease risk in young overweight women. COP training improved weight and body composition better than the FATmax exercise, while the latter provided greater improvements in serum ApoAI levels.